2006
DOI: 10.1113/jphysiol.2006.115766
|View full text |Cite
|
Sign up to set email alerts
|

A spinal vasopressinergic mechanism mediates hyperosmolality‐induced sympathoexcitation

Abstract: An elevation in plasma osmolality elicits a complex neurohumoral response, including an activation of the sympathetic nervous system and an increase in arterial pressure. Using a combination of in vivo and in situ rat preparations, we sought to investigate whether hypothalamic vasopressinergic spinally projecting neurones are activated during increases in plasma osmolality to elicit sympathoexcitation. Hypertonic saline (HS, I.V. bolus), which produced a physiological increase in plasma osmolality to 299 ± 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
127
2
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(157 citation statements)
references
References 72 publications
16
127
2
12
Order By: Relevance
“…Taken together, our results support a functionally relevant P2-AMPA receptor cross talk in PVN-RVLM neurons, which contributes to ATP-mediated excitatory effects on PVN sympathetic neurons. Moreover, our studies indicate that the P2-AMPA receptor coupling is engaged during an osmotic challenge, being thus a potential mechanism contributing to increased PVN neuronal activation and the enhanced sympathoexcitation evoked during this physiological challenge (Antunes et al 2006;Stocker and Toney 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our results support a functionally relevant P2-AMPA receptor cross talk in PVN-RVLM neurons, which contributes to ATP-mediated excitatory effects on PVN sympathetic neurons. Moreover, our studies indicate that the P2-AMPA receptor coupling is engaged during an osmotic challenge, being thus a potential mechanism contributing to increased PVN neuronal activation and the enhanced sympathoexcitation evoked during this physiological challenge (Antunes et al 2006;Stocker and Toney 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that acute osmotic stimulation by intravenous hypertonic saline or mannitol solution induces a PVN-dependent sympathoexcitatory response (Antunes et al 2006;Badoer et al 2003;Chen and Toney 2001;Son et al 2013;Stocker and Toney 2005). Thus, on the basis of results outlined above, we addressed whether an osmotic challenge (aCSF containing mannitol 1%, 1 min) could engage a purinergic-AMPA receptor cross talk in PVN sympathetic neurons.…”
Section: Atp-mediated Potentiation Of I Ampa In Pvn-rvlm Neurons Depementioning
confidence: 99%
“…The PVN parvocellular division is an important integrative structure that regulates coordinated responses to perturbations in cardiovascular homeostasis, such as dehydration. Through descending projections from parvocellular neurons to the brainstem and spinal cord (Sawchenko and Swanson, 1982), the PVN directly regulates changes in sympathetic nerve activity involved in blood pressure and blood volume regulation (Toney et al, 2003;Antunes et al, 2006). The role of these novel PVN transcription factors in the coordinated cardiovascular response to an osmotic stimulus will be a focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment involving the co-infusion of phenylephrine was repeated, in rats pre-treated with prazosin, to investigate if prazosin (a α 1 adrenergic receptor antagonist) will give answers to questions that were not answered above. The dose of prazosin (1 mg/kg) used in this study, has been previously used by other researchers (Nagai et al, 2003;Dabire, 2004;Antunes et al, 2006;Wang et al, 2006;Braga et al, 2008;PintÉRovÁ et al, 2009;Wong et al, 2011) …”
Section: Does T Violacea Act By Blocking the Alpha I Adrenoceptors?mentioning
confidence: 99%
“…Dilutions below and above the doses used in literature were tested to obtain the lowest dose that produced an effect on BP and /or HR, as well as the maximum effect, which was not lethal in the SHR used in the study. The animals were The doses of losartan (30 mg/kg) (Wong et al, 1990;Choi et al, 2009a;Susic et al, 2009b), and prazosin (1 mg/kg) (Nagai et al, 2003;Dabire, 2004;Antunes et al, 2006;Wang et al, 2006;Braga et al, 2008;PintÉRovÁ et al, 2009) were obtained from literature.…”
Section: Materials Used In the Anaesthetized Hypertensive Rat Modelmentioning
confidence: 99%